(untitled) (Baghdad Science Journal, 2004)
The effect ©? acid and alkility for the dichromate solution and the thicknness of gelatin layer on the effecincy of the film , also the time period between the recording and the reconstraction processes . the last effecincy was 90% for PH=5.6 and 95% for d=110 ?? . the highe effeciny for time period was 82% for 48 h .